A Study on Job Satisfaction Among Employees in an Automobile Sales and Service Company - Eapen, Mary; Annamalai, Sumathi (Prabandhan: Indian Journal of Management, 2015)
An organization being in the service industry has to maintain a large pool of staff both at the front end as well as at the back end operations. Hence, it becomes critical to enhance employee job satisfaction levels to increase productivity and thereby, sales. The present study focuses on the job satisfaction levels and the major factors that contribute to job satisfaction. It sheds some light on how job satisfaction varies with age, gender, department, tenure, and job role of the employee. It also aimed to capture the employees’ suggestions on improvement areas that would, in turn, help to achieve higher job satisfaction levels in the future. The results showed that 89% of the employees were either satisfied or were very satisfied with their current job. The major factors that contributed to job satisfaction were working relationship with supervisor, pay, benefits and development, work environment, leadership and support, prioritized values, security, and clarity of communication. Hypotheses testing showed no strong relationship between job satisfaction and age, gender, department, work tenure, or job role of the respondents.